Isolasi Gelatin dari Tulang Ikan Gulamah (Johnius trachycephalus) dan Aplikasinya Pada Permen Jelly - Sindi, Sindi; Yuniarti , Rafita; Lubis , Minda Sari; Rani , Zulmai (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
Background: Gelatin, as a product of partial collagen hydrolysis, is typically derived from pig bones or skin, creating halal compliance issues for Indonesia's Muslim population. Objective: This study aimed to isolate halal gelatin from gulamah fish bones (Johnius trachycephalus) and apply it as a gelling agent in jelly candy production. Methods: The gelatin isolation process involved: (1) degreasing through immersion in boiling water, (2) demineralization using 5% acetic acid for 48 hours, (3) extraction at 60-75°C for 12 hours, and (4) oven drying at 50°C. Gelatin was characterized using FTIR and tested for quality parameters (yield, moisture content, ash content, pH) according to SNI standards. Jelly candies were formulated with two gelatin concentrations (F1=5g; F2=10g) and evaluated for physical properties and hedonic quality. Results: The study achieved a gelatin yield of 7.32% with SNI 06-3735 compliant characteristics: 10.2% moisture content, 1.24% ash content, pH 6.28, and FTIR identification of characteristic functional groups (-OH, C=O, N-H, C-H, and C-N). Formula F2 (10g gelatin) received the highest preference scores for texture (2.93), aroma (2.93), and taste (4.63). Conclusion: Gulamah fish bones show potential as a halal gelatin source meeting quality standards, with optimal application at a 10g concentration in jelly candy formulations